2013
DOI: 10.2478/sampre-2013-0005
|View full text |Cite
|
Sign up to set email alerts
|

Microextraction using packed sorbent as an effective and high-throughput sample extraction technique: Recent applications and future trends.

Abstract: In the last decade, several developments, particularly in the liquid chromatography and hyphenated techniques fields, have allowed researchers to reach analytical limits that are becoming very close to the single molecule level. Sample preparation, however, despite being a key step in the analytical methodology, did not track these developments and very few approaches able to cope with these stringent analytical requirements were developed. One such approach is microextraction by packed sorbent (MEPS), a sophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(49 citation statements)
references
References 112 publications
0
48
0
1
Order By: Relevance
“…This indicates that more advanced extraction techniques need to be developed. In this context, Abdel-Rehim [25] developed in 2004 the microextraction by packed sorbent (MEPS) a powerful technique based on the miniaturization of conventional SPE technique [26]. When compared to other extraction techniques, MEPS is very versatile, since its cartridge can be packed with any solid-phase material such as silica-based (C2, C8, C18), restricted access material (RAM) or molecularly imprinted polymers (MIPs) and can reduce the volume of solvent and sample needed [27].…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that more advanced extraction techniques need to be developed. In this context, Abdel-Rehim [25] developed in 2004 the microextraction by packed sorbent (MEPS) a powerful technique based on the miniaturization of conventional SPE technique [26]. When compared to other extraction techniques, MEPS is very versatile, since its cartridge can be packed with any solid-phase material such as silica-based (C2, C8, C18), restricted access material (RAM) or molecularly imprinted polymers (MIPs) and can reduce the volume of solvent and sample needed [27].…”
Section: Introductionmentioning
confidence: 99%
“…This involves the dilution of the sample (to reduce the sample viscosity), pH adjustment (to reduce the ionization of weak acids and bases for reversed-phase extraction), deproteination (with previous protein precipitation, for instance) and sample loading speed adjustment (an option in semi-automatic and automatic MEPS (reviewed in [9,35]).…”
Section: Extraction Techniquesmentioning
confidence: 99%
“…Microextraction techniques (METs), which use a minimal extractant amount (sorbent or liquid phase) offer these benefits and are becoming widely used in different fields, such as the biomedical, food, forensic and environmental ones, just to name the most frequently described applications (reviewed in [8,9,10,11,12,13]).…”
Section: Introductionmentioning
confidence: 99%
“…Since a small amount of sorbent is used, only relatively small amounts of solvents are needed for elution of the analytes from the adsorbent. MEPS has been employed for the analysis of drugs, pesticides, polycyclic aromatic hydrocarbons and other organic pollutants in environmental water samples (reviewed in Pereira et al ., ). It has also been successfully applied to the qualitative and quantitative determination of a wide variety of drugs and/or metabolites in biological samples, such as plasma, serum, blood, urine, saliva and hair (Abdel‐Rehim, ; Alves et al ., ; Aufartová et al ., ; Bagheri et al ., ; Fu et al ., ; Gonçalves and Câmara, ; Moreno et al ., ; Noche et al ., ; Nováková and Vlčková, ; Rodrigues et al ., ; Said et al ., , ; Samanidou et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…A more detailed description of MEPS sorbent properties and target analyte extraction was recently provided by Pereira et al . (). Later in this review we will discuss other promising customized MEPS sorbents that have been reported, such as those using molecular imprinting polymers (MIPs) and carbon nanotubes.…”
Section: Introductionmentioning
confidence: 99%